Hypotaurine effect on the bovine oocyte in- vitro maturation and fertilization - Elhussiney, Aya M.; Aggag, Mohsen A.; Badr, Magdy R.; Elkhawagah, Ahmed R.M.; Sousa, Gamal A. (Journal of Advanced Veterinary Research, 2025)
The objective of the present research was to examine the impact of various concentrations of Hypotaurine (0, 10, 15 and 20 µM /ml) on the bovine oocytes’ in- vitro maturation and fertilization rates as well as on the enzymatic activity of lipid-peroxidation and antioxidants. Bovine ovaries were harvested from El-Mounib slaughterhouse in Giza Governorate, Egypt. The oocytes were aspirated from medium sized follicles (4-8 mm). The selected oocytes were matured in- vitro in TCM-199 media supplemented with different concentrations of Hypotaurine. Some of the matured oocytes were evaluated for their maturation rates (nuclear & cytoplasmic maturation), and the maturation media were analyzed to determine the lipid peroxidation levels (Malondialdehyde, MDA), and various antioxidant enzymes, including glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD). The other mature oocytes were in- vitro fertilized and examined for the fertilization rate and the different stages of embryonic development. The results represented that Hypotaurine at a concentration of 10 µM /ml significantly (P≤0.05) improved the maturation rate of oocytes (MII), the fertilization rate and the different stages of embryo development. In addition, Hypotaurine decreased the level of lipid peroxidation (MDA) significantly (P≤ 0.05) and increased the antioxidants levels (CAT, GSH, and SOD), especially at a concentration of 10 µM /ml. In conclusion, Hypotaurine improved the bovine oocyte in- vitro maturation and fertilization, with the effect being clearly noticeable at a concentration of 10 µM /ml.